Notes on the distribution of Palearctic Scythrididae (Lepidoptera: Gelechioidea) - P. Passerin d'Entrèves; A. Roggero (SHILAP, 2010)
In the paper new records of Scythrididae distribution are reported from some areas of the Eastern Palearctic Region that are yet poorly known, as Iran, Afghanistan, Pakistan, Tajikistan and Mongolia. New data from various parts of the SW Palearctic Region (Algeria, Lebanon, Jordan and Turkey) are provided as well. Current knowledge of Scythrididae species distribution is significantly increased thanks to the new records here provided, 3 new species from Iran, 1 new species from Afghanistan, 2 new species from Tajikistan, 1 new species from Pakistan, 1 new species from Mongolia and 1 new species from Turkey. Taxonomic remarks are also furnished for the recorded species. Furthermore, the 97 scythridid species from SW Irano-Turanian region are listed here.